(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The present study aimed to know the effect of the aqueous extract of zingiber plant roots in preventing the damage caused by injecting Syrian hamsters with 1,2 dimethyl hydrazine (DMH). The control, the rest of the groups were divided into 20 individuals for each group, the second and third groups dosed zingiber extract (80 mg/kg, 220 mg/kg) respectively, and the fourth group was injected with DMH at a concentration of 40 mg/kg peritoneally through the abdomen at a rate of 4. times/week for 8 weeks, the fifth and sixth groups dosed with zingiber extract (80 mg/kg, 220 mg/kg) for a week, then they were dosed with the plant extract simultaneously with DMH injection A study of the histological sections of the colon in animals injected with DMH showed the development of cancerous tumors by 80%. The second and third groups did not suffer from any changes in the structure of the colon tissue. The tissue structure improved in the fifth group, but it returned to its normal structure in the sixth group in terms of cells and glands, which Emphasizes the importance of the aqueous extract of zingiber in protecting colon tissue, improving cell structure, and preventing oxidative stress induced by 1,2 dimethyl hydrazine. .